Islamic Philosophy and Artificial Intelligence: Mapping the Terrain - Qusthan A.H. Firdaus; Aktobi Ghozali; Azzimma Siswoyo Alghifary (Aqlania, 2025)
The development of artificial intelligence (AI) is progressing through stages: artificial narrow intelligence (ANI), artificial general intelligence (AGI) and artificial super intelligence (ASI). This article aims to map out recent literature in Islamic philosophy which discusses and explores AI with respect to those divisions. In other words, this is a baseline study on the potential discourse of AI within the various schools of Islamic philosophy such as masha’ī (peripatetic), ishraqī (illuminationist), and sadranī (transcendental). Our inquiry concerns with how do contemporary scholars in Islamic philosophy give response to the recent development of AI? We seek various open access English references which discuss AI and Islamic philosophy, and we discover 19 English references published in between 2014-2024. We take the initiative to broaden our investigation to include 12 Arabic references. Although classical Islamic philosophy contains a significant number of discussions on intellect and mind, this has not been sufficient to attract more research on AI and Islamic philosophy. Therefore, we present and identify some questions to stimulate further academic research on AI within Islamic philosophy.